BASICS OF DEVELOPING THE QUALITY OF ENDURANCE IN CADETS (Modern education and development, 2024)
Endurance is the quality of the human body to overcome the impending fatigue. Distinguish between physical, emotional, emotional and mental fatigue. In physical education, all types of fatigue are in different proportions, but physical fatigue is most important. Therefore, the whole technique described below is associated with the development of physical endurance.